Impulsivity in internet addiction: a comparison with pathological gambling - Lee, Hae Woo; Choi, Jung-Seok; Shin, Young-Chul; Lee, Jun-Young; Jung, Hee Yeon; Kwon, Jun Soo (Cyberpsychology, behavior and social networking, 2012)
Internet addiction has been considered to be associated with poor impulse control. The aim of this study is to compare the trait impulsivity of those suffering from Internet addiction with that of individuals suffering from pathological gambling. Twenty-seven patients diagnosed with Internet addiction (age: 24.78±4.37 years), 27 patients diagnosed with pathological gambling (age: 25.67±3.97 years), and 27 healthy controls (age: 25.33±2.79 years) were enrolled in this study. All patients were men seeking treatment. Trait impulsivity and the severity of the Internet addiction and pathological gambling were measured by the Barratt Impulsiveness Scale-11, the Young's Internet Addiction Test, and the South Oaks Gambling Screen, respectively. The Beck Depression Inventory and the Beck Anxiety Inventory were also administered to all subjects. Our results show that those suffering from Internet addiction showed increased levels of trait impulsivity which were comparable to those of patients diagnosed with pathological gambling. Additionally, the severity of Internet addiction was positively correlated with the level of trait impulsivity in patients with Internet addiction. These results state that Internet addiction can be conceptualized as an impulse control disorder and that trait impulsivity is a marker for vulnerability to Internet addiction.